PROFESSIONAL MOBILITY AS A FACTOR OF BORDER GUARDS READINESS FOR PROFESSIONAL ACTIVITY: UKRAINIAN AND EUROPEAN EXPERIENCE - Islamova, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article presents an analysis and generalization of approaches to the nature and content of professional mobility. It is concluded that professional mobility is directly interrelated with readiness to work in the specialty, since these two concepts have common elements in the structure, in particular professional knowledge, abilities, skills and professionally important qualities. Taking into account the results of the analysis of research related to the problem of professional mobility, it was found out that this concept can be defined as readiness and ability to work in the context of transformation of professional (production, service) tasks, development of new specialties or changing them. Professional mobility covers the ability to successfully switch to another activity or change types of activities, effectively use the system of generalized professional techniques to perform any tasks in the professional sphere, and it is relatively easy to move from one type of activity to another. For professional mobility, it is important to have a high level of generalized professional knowledge, experience in improving them and obtaining them independently. The results of the review of publications on the research topic suggest that there are two types of mobility – horizontal and vertical. Horizontal mobility involves the transition of an individual or social object from one social position to another, which is at the same level, as well as a change of place of residence. As for vertical mobility, it involves the transition of an individual or social object from one social position to another. It was found out that mobility is an integrative property that is formed and developed during practical, educational, social, socio-cultural activities of a person and provides him with the opportunity to realize his inclinations, abilities, opportunities. It was found that in the context of training of border guard agencies’ personnel in the EU, professional mobility of border guards is ensured by their high level of interoperability, which is a necessary condition for effective organization of protection of EU external borders by representatives of various European border guard agencies. The most common form of ensuring the professional mobility of European border guards is working within the Permanent Corps of the European Border and Coast Guard Agency Frontex. The training of Ukrainian Border Guard Agency’s staff in the context of European integration requires the study of the experience of border agencies in EU countries to provide conditions for the development of professional mobility of border guards, which requires further thorough study of the outlined topic.